Hypomethylation of intron1 of α-synuclein gene does not correlate with Parkinson's disease. Issue 1 (December 2017) - Guhathakurta, Subhrangshu; Evangelista, Baggio; Ghosh, Susmita; Basu, Sambuddha; Kim, Yoon-Seong
Abstract Deregulation of α-synuclein encoding gene (SNCA ) is one of the important facets of Parkinson's disease (PD) research. DNA methylation status ofSNCA -intron1 has been shown to regulate the α-synuclein expression. The present study is aimed at investigating whether methylation ofSNCA -intron1 is associated with higher expression of α-synuclein in PD. We have investigated the intron1 methylation status from 16 post-mortem brain samples comprised of 8 PD and 8 control subjects using bisulfite sequencing. We further correlated this methylation status with α-synuclein protein levels in substantia nigra of that individual using western blot analysis. We did not observe any significant difference in methylation ofSNCA -intron1 region between PD and control samples. Moreover, no correlation was observed between methylation ofSNCA -intron1 with α-synuclein level. Methylation ofSNCA -intron1 region does not correlate with α-synuclein expression in PD samples.